2018
DOI: 10.1093/jxb/ery185
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of organelles to plant intracellular calcium signalling

Abstract: Calcium (Ca2+) is among the most important intracellular messengers in living organisms. Understanding of the players and dynamics of Ca2+ signalling pathways in plants may help to unravel the molecular basis of their exceptional flexibility to respond and to adapt to different stimuli. In the present review we focus on new tools that have recently revolutionized our view of organellar Ca2+ signalling as well as on the current knowledge regarding the pathways mediating Ca2+ fluxes across intracellular membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
107
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 241 publications
2
107
0
Order By: Relevance
“…As the Ca 2+ concentration of water is in the millimolar range, which is above the equilibrium dissociation constant of various forms of ATP to Ca 2+ and would therefore be toxic to the cell, cells have evolved ways to decrease the Ca 2+ concentration using pumps, transporters, and buffers. Cells typically maintain cytosolic free Ca 2+ concentrations at resting levels of ;50-200 nM, resulting in a substantial chemical Ca 2+ gradient among the cytosol, the extracellular space, and intracellular compartments (e.g., vacuole and endoplasmic reticulum) (Stael et al, 2012;Costa et al, 2018). Besides, the net electrical potentials existing across the plasma membrane (PM) and tonoplast contribute to building up large electrochemical gradients to drive for Ca 2+ transport.…”
Section: Introductionmentioning
confidence: 99%
“…As the Ca 2+ concentration of water is in the millimolar range, which is above the equilibrium dissociation constant of various forms of ATP to Ca 2+ and would therefore be toxic to the cell, cells have evolved ways to decrease the Ca 2+ concentration using pumps, transporters, and buffers. Cells typically maintain cytosolic free Ca 2+ concentrations at resting levels of ;50-200 nM, resulting in a substantial chemical Ca 2+ gradient among the cytosol, the extracellular space, and intracellular compartments (e.g., vacuole and endoplasmic reticulum) (Stael et al, 2012;Costa et al, 2018). Besides, the net electrical potentials existing across the plasma membrane (PM) and tonoplast contribute to building up large electrochemical gradients to drive for Ca 2+ transport.…”
Section: Introductionmentioning
confidence: 99%
“…A complex Ca 2+ homeostatic and signaling machinery allows for a tight regulation of the intracellular concentration of the ion ([Ca 2+ ]) and its variations during signal transduction (Kudla et al, 2018). Plant organellar Ca 2+ signaling is a rapidly expanding field of investigation, also thanks to the increasing availability of novel genetically encoded Ca 2+ indicators, specifically targeted to different intracellular compartments (Costa et al, 2018). In addition to the vacuole, considered as the main stimulus-releasable Ca 2+ store in the plant cell, other organelles, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the Golgi as an important Ca 2+ store that contributes to Ca 2+ signaling in animal cells is established (Pizzo et al ., 2011). Although information on Ca 2+ handling by the plant Golgi is scarce (Costa et al ., 2018), it has been shown that free Ca 2+ concentration is higher in the Golgi than in the cytosol of plant cells, and abiotic cues can affect luminal Ca 2+ dynamics (Ordenes et al ., 2012). The nature and identity of Ca 2+ channels and transporters of the plant Golgi awaits clarification, although a role for P2A-type ATPase AtECA3 in the transport of Ca 2+ and Mn 2+ into the Golgi has been proposed (Mills et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…AtGAAP2/3/5, but not AtGAAP1/4, also localized in the tonoplast (Figure 5). The vacuole is the main storage compartment of Ca 2+ in plant cells (Peiter, 2011; Costa et al ., 2018) and many tonoplast Ca 2+ transporters have been identified (Martinoia et al ., 2012; Neuhaus and Trentmann, 2014; Costa et al ., 2018). Ca 2+ release from the vacuole likely contributes to signaling in plants and here evidence for a role for TPC1 as a tonoplast channel critical for many physiological processes is accumulating (Peiter et al ., 2005; Carpaneto and Gradogna, 2018).…”
Section: Discussionmentioning
confidence: 99%